Legal Analysis Of Human Trafficking Through Platforms Based On Indonesian Laws And Regulations - Pasaribu, Andreas Okta; Siregar, Mhd Azhali (JURNAL HUKUM SEHASEN, 2025)
This research analyzes legal protection against human trafficking that can be downloaded via video via social media platforms. Which in this case is often found in social media platform applications where videos contain pornographic elements and it is not uncommon for users to also trade themselves to viewers of the application by including a link that can be accessed by viewers thereby directing them to the application. owner's personal account contact. so that you can carry out the transaction. Thus, this act can be categorized as an act of human trafficking where the person indirectly hands over their rights to something to another person by obtaining an imbalance of economic value that will benefit both parties unlawfully. This research was carried out using a descriptive approach with qualitative methods with a type of normative juridical research based on secondary data sources taken from case studies of court decisions and statutory regulations with analysis using related legal materials. The results of this research obtained results in the form of knowledge regarding forms of legal protection against criminal acts of trafficking in persons carried out through video-based social media platforms which do not contain elements of criminal acts of trafficking in persons as contained in article 40 paragraph 2. and paragraph 2(a) which reads : "The government protects the interests of the public from all types of interference due to the coding of Electronic Information and Electronic Transactions which interfere with public transmissions, in accordance with the provisions of laws and regulations." and the Government is obliged to prevent in the form of blocking websites and prevent the distribution and use of Electronic Information and/or Electronic Documents containing prohibited content in accordance with the provisions of laws and regulations."